Innovate by innovating: A reflection for university management - Correa, Rodrigo; Paguay Chávez, Félix Wilmer (SATHIRI, 2019)
The present research of qualitative approach and non-experimental modality, allowed to make a documentary review in order to understand the methodologies and tools used for the addition of innovation in educational institutions, their implementation and the main actors. In that sense, the possible sources of innovation for university management, according to specialized literature, are: prospective evaluation, risk management and process management that require rethinking the substantive elements of the university and considering the learning spaces, pedagogy and ICT, as the dimensions that can be linked to innovation, at least since teaching.